2019
DOI: 10.1002/oby.22627
|View full text |Cite
|
Sign up to set email alerts
|

Ratio of Conjugated Chenodeoxycholic to Muricholic Acids is Associated with Severity of Nonalcoholic Steatohepatitis

Abstract: Objective Bile acids (BAs) are important molecules in the progression of nonalcoholic fatty liver disease. This study aimed to investigate BA profile alterations in Chinese nonalcoholic steatohepatitis (NASH) patients. Methods BA profiles in serum and liver tissues were determined by ultraperformance liquid chromatography coupled to tandem mass spectrometry in patients from two different clinical centers. Results A total of 134 participants were enrolled in this study to serve as the training (n = 87) and vali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 44 publications
1
22
0
1
Order By: Relevance
“…Thus, increased primary BA production through the classical synthesis compensates for low hepatic exposure to BAs, but completely changes the balance between primary and secondary BAs secreted by the liver. Our data in preclinical models are similar to reports of upregulated CYP7A1 expression and increased BA synthesis in livers of NASH vs. no-NASH patients, 23 , 25 , 27 which indicate reduced FXR signaling.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Thus, increased primary BA production through the classical synthesis compensates for low hepatic exposure to BAs, but completely changes the balance between primary and secondary BAs secreted by the liver. Our data in preclinical models are similar to reports of upregulated CYP7A1 expression and increased BA synthesis in livers of NASH vs. no-NASH patients, 23 , 25 , 27 which indicate reduced FXR signaling.…”
Section: Discussionsupporting
confidence: 90%
“…Literature reports that explore the association between BA composition and NAFLD are discordant. [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] Proper interpretation of available data is difficult and speculative because the sampling of BAs in humans is often restricted to systemic blood and feces, as sampling of enterohepatic BAs is challenging. BAs in feces and systemic blood have escaped the enterohepatic cycle and thereby do not reflect the BA cycling between the liver and the gut.…”
Section: Introductionmentioning
confidence: 99%
“…The detergent effect of bile acids can inhibit certain types of bacteria but not others so that the balanced growth of various commensal bacteria is well maintained. Chen et al (2019) found that the conjugated chenodeoxycholic acid/muricholic acid ratio was associated with NASH severity in 134 human NAFLD subjects [ 20 ]. Decreased deconjugation could also result in decreased production of taurine.…”
Section: Gut Microbiota Metabolites In the Pathogenesis Of Nafldmentioning
confidence: 99%
“…Bile acids NASH Primary and secondary bile acids are increased [26] NASH C4 increased [29] NASH Primary and secondary bile acids increased [30] NASH Bile acids increase with NASH progression [31] NASH Bile acids increased [32] NASH Primary bile acids increased, secondary decreased [33] NAFLD Total bile acid are decreased but major difference is in composition, bile acid level increases with fibrosis progression [34] NAFLD Bile acids change with disease progression, direction depended on the type of bile acid [35] NASH Primary conjugated bile acid increase with fibrosis, unconjugated bile acids decrease [36] NAFLD Primary and secondary bile acids are increased in higher fibrotic stages, but no change in C4 [27] Polyunsaturated fatty acids (PUFA) NAFLD Decreased [35] Severe NAFLD Total PUFA decreased in red blood cell membrane, n-3 all decreased, n-6 majority increased, except linoleic acid decreased [37] NAFLD Total PUFA n-3 decreased in serum [38] NAFLD Total PUFA decreased in erythrocytes [39] NASH PUFA (18:3n-3) decreased [9] NASH Eicosapentaenoate (20:5n-3), docosahexaenoate (22:6n-3), arachidonate (20:4n-6) are decreased [32] NASH PUFA are altered [40] Monounsaturated fatty acids (MUFA) NASH Total MUFA increased [40] Severe NAFLD Total MUFA increased in red blood cell membrane [37] NAFLD Total MUFA increased, docosahexaenoic acid (C22:6) and arachidonic acid (C20:4) decreased in blood [41] Sphingolipids NASH Sphingomyelin (36:0) increased [42] NAFLD Sphingomyelins decreased [43] NASH Sphingomyelin increased [9] Ketones NASH Decreased [44] Branched amino acids NAFLD All three increased [43] NASH All three increased [32] PPARα NASH Decreased mRNA expression in liver, negative correlation with NASH progression [45,46] LXR, SREBPC1 NAFLD Increased mRNA and protein expression in liver [47] PPARγ NAFLD PPARγ2 mRNA is increased in liver [48] VDR...…”
Section: Metabolitesmentioning
confidence: 99%